2006
DOI: 10.1007/s10340-006-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma radiation on life stages of the Mediterranean flour moth, Ephestia kuehniella Zeller (Lepidoptera: Pyralidae)

Abstract: We report the results of experiments conducted with Ephestia kuehniella Zeller to determine the effects of gamma radiation on life stages. Eggs, larvae, pupae and adults were irradiated with increas-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 23 publications
2
22
0
2
Order By: Relevance
“…Due to its weak penetrating power, however, eggs have to be treated in a very thin layer which may limit its applications, or high quality, more expensive machines are to be used. Ionizing radiation, particularly gamma radiation, has a very high penetrating ability and has been used for killing insect eggs before (Brower 1982;Tilton and Brower 1983;Toba and Burditt 1992;Mansour 2004;Ayvas and Tuncbileck 2006;Ayvaz et al 2008b). Elbadry (1965) suggested that moths eggs exposed to gamma radiation could serve as a food resource for Trichogramma rearing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its weak penetrating power, however, eggs have to be treated in a very thin layer which may limit its applications, or high quality, more expensive machines are to be used. Ionizing radiation, particularly gamma radiation, has a very high penetrating ability and has been used for killing insect eggs before (Brower 1982;Tilton and Brower 1983;Toba and Burditt 1992;Mansour 2004;Ayvas and Tuncbileck 2006;Ayvaz et al 2008b). Elbadry (1965) suggested that moths eggs exposed to gamma radiation could serve as a food resource for Trichogramma rearing.…”
Section: Introductionmentioning
confidence: 99%
“…In order to determine the irradiation dose, however, the radiosensitivity of the eggs has to be investigated. Ayvas and Tuncbileck (2006) studied the effects of gamma radiation on a mixture of 1-3-day-old E. kuehniella eggs and found that 400 Gy dose (the highest used dose) reduced egg hatch to less than 27%. Because this dose did not completely stop egg hatch and eggs [2 day old are not suitable for T. cacoeciae rearing, the radiosensitivity of E. kuehniella eggs of a younger age needs to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Dose-dependent developmental delay was also reported for the irradiated eggs and larvae of T. castaneum (Mehta et al 1990). Increasing post-treatment longevity for irradiated P. inw terpunctella, the false codling moth, Cryptophlebia leucow treta Meyrick, and the Mediterranean flour moth, Ephestia kuehniella, have been reported previously (Johnson and Vail 1988;Bloem et al 2003;Azelmat et al 2005;Ayvaz and Tuncbilek 2006). Typically, irradiated nymphs or larvae would have a prolonged nymphal or larval stage and might live longer than non-irradiated control insects (Hasan and Khan 1998).…”
Section: Discussionmentioning
confidence: 78%
“…The minimum dose required to prevent adult emergence of Plodia iterpunctella from larvae was 300 Gy, while doses required to cause death were 450 Gy and above (Azelmat et al 2005). A dose of 250 Gy was sufficient to cause complete mortality for last-instar larvae of Ephestia kuehniella Zeller (Ayvaz and Tuncbilek 2006). No codling moth larvae reached adulthood when larvae were irradiated with 200 Gy (Mansour 2003).…”
Section: Discussionmentioning
confidence: 98%
“…Zararlı böcekleri kontrol altına almada radyasyon kullanımı birçok çevre (Uluslararası Atom [16]. Plodia interpunctella (Hubner) (Lepidoptera:…”
Section: Introductionunclassified